2005
DOI: 10.1159/000087661
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand Therapy with Pantoprazole 20 mg as Effective Long-Term Management of Reflux Disease in Patients with Mild GERD: The ORION Trial

Abstract: Aims: To compare safety and efficacy of on-demand pantoprazole 20 mg/40 mg versus placebo in the long-term management of patients with mild gastroesophageal reflux disease (GERD) after heartburn relief. Methods: A total of 634 patients with endoscopically confirmed GERD grade 0/I and heartburn were included. During the acute phase, patients were treated with pantoprazole 20 mg once daily for 4 weeks. Those patients relieved from heartburn entered the long-term phase, and were randomly assigned to either treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Monotherapy results in mean daily consumptions of 0.3–1 tablet a day [11,12,21,22], whereas in combination with antacids, needs of <0.5 PPI tablet a day were reported [23,24,25,26,27]. In all these studies, first-time consulting patients were included and on-demand treatment was initiated after a short period of standard treatment, which is the most ideal situation for titrating PPI needs.…”
Section: Discussionmentioning
confidence: 99%
“…Monotherapy results in mean daily consumptions of 0.3–1 tablet a day [11,12,21,22], whereas in combination with antacids, needs of <0.5 PPI tablet a day were reported [23,24,25,26,27]. In all these studies, first-time consulting patients were included and on-demand treatment was initiated after a short period of standard treatment, which is the most ideal situation for titrating PPI needs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a lower endoscopic recurrence rate was found in the group receiving the dose of 20 mg/day than in the group receiving the dose of 10 mg/day (7). On the other hand, in the study of Scholten et al (16), no difference was found between patients using pantoprazole at the standard dose and at the maintenance dose at the end of the 6 th month in terms of the mean symptom load (2.7 vs. 2.9, p>0.05). Similarly, at the end of the 6 th month, there was no difference between patients receiving esomeprazole at the standard dose and at the maintenance dose with regard to symptomatic remission rates (17).…”
Section: Recommendationsmentioning
confidence: 76%
“…3,4 Inhibition of STAT3 with several agents has also been shown to lead to growth inhibition and enhanced chemo-sensitivity in HCC cells, supporting the role of STAT3 in HCC development. [5][6][7] In conclusion, based on the above observations, it is reasonable to suggest a potential link between obesity and HCC via activation of STAT3. Although it is widely agreed that IL-6-and TNF-mediated STAT3 activation plays a major role in the development of HCC, the association with obesity still warrants further clinical investigation.…”
mentioning
confidence: 76%
“…The study is instructive in three ways: first, although similar studies have been performed in Europe, [2][3][4][5][6] there is evidence of differences to responses to PPI [7][8][9] and indeed in the pathogenesis of GERD in different ethnic groups. 10 Therefore, it is essential to confirm that the findings from European studies are indeed applicable to the US population at large, which is ethnically different in make-up to the European population.…”
Section: Acknowledgementmentioning
confidence: 99%